2010
DOI: 10.1590/s0004-28032010000100004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sour taste and cold temperature in pharyngeal transit duration in patients with stroke

Abstract: -Context -The effect of sour taste and food temperature variations in dysphagic patients has not been entirely clarified.Objective -To determine the effect of sour and cold food in the pharyngeal transit times of patients with stroke. Methods -Patients participating in this study were 30 right-handed adults, 16 of which were male and 14 were female, aged 41 to 88 (average age 62.3 years) with ictus varying from 1 to 30 days (median of 6 days). To analyze the pharyngeal transit time a videofluoroscopy swallow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 29 publications
2
31
0
4
Order By: Relevance
“…Pré-fonterapia a deglutição do paciente apresentava 13 segundos de TTF, quando na siologia normal este tempo não excede de 1 a 2 segundos, caracterizando a grande di culdade do paciente em desencadear a resposta faríngea. Em pacientes pós-AVE, a alteração de TTF já foi discutida, tanto com relação à mudança no tempo como também sobre os marcadores que de nem o início da fase faríngea 14,31,32 . No entanto, não foram encontrados trabalhos na literatura que tivessem utilizado os softwares de medição de tempo de trânsito orofaríngeo para avaliar o desempenho da dinâmica da deglutição pré e pós-fonoterapia.…”
Section: Discussionunclassified
“…Pré-fonterapia a deglutição do paciente apresentava 13 segundos de TTF, quando na siologia normal este tempo não excede de 1 a 2 segundos, caracterizando a grande di culdade do paciente em desencadear a resposta faríngea. Em pacientes pós-AVE, a alteração de TTF já foi discutida, tanto com relação à mudança no tempo como também sobre os marcadores que de nem o início da fase faríngea 14,31,32 . No entanto, não foram encontrados trabalhos na literatura que tivessem utilizado os softwares de medição de tempo de trânsito orofaríngeo para avaliar o desempenho da dinâmica da deglutição pré e pós-fonoterapia.…”
Section: Discussionunclassified
“…There is considerable evidence that sour taste facilitates swallow initiation. 41) We tested the effects of water, sour solutions, and other taste solutions applied to the mucosa of the pharyngolaryngeal region on swallow initiation in anesthetized rats, and showed that acetic and citric acids, which provide a sour taste, had a stronger facilitatory effect on swallow initiation as compared with other taste solutions 15) (Fig. 3).…”
Section: Inputs From Taste Receptors (Animal Study)mentioning
confidence: 99%
“…The influence of sour taste and cold temperature in pharyngeal transit duration in patients with stroke Cola et al (22) 2010…”
Section: Neuromuscular Electricalmentioning
confidence: 99%